Efektivitas Metode Pendekatan Multidisipliner dalam Pembelajaran di Tingkat Sekolah Dasar - Indah Fadilah Pelupessy; Hindun Hindun (Universitas Maritim AMNI Semarang, 2024)
A multidisciplinary approach is a method in education that combines various disciplines to create a better understanding. This approach recognizes that the real world is not divided into separate categories of knowledge, therefore it tries to bring together various disciplines so that students can see the connections between concepts. This study aims to evaluate the effectiveness of the multidisciplinary approach method in the context of learning at the primary school level. The background of this research is based on the need to develop a holistic learning approach that suits the needs of today's children. A literature study was conducted to determine the concept of multidisciplinary approach and its impact on learning achievement and development of primary school children. The literature study method was used to collect, review and synthesize related research findings. This research is expected to provide in-depth insight into the potential application of the multidisciplinary approach in learning at the primary school level. The practical implications of the findings can provide direction for the development of more effective curriculum and teaching methods at the primary school level.